CHILEAN COMUNISTY PARTY AND THE PLOT OCCUPATION UNDER DICTAROSHIP: THE “FIGHTING” FOR HOUSING, 1980-1984 - Reyes Soriano, Jaime (Revista de Historia Social y de las Mentalidades, 2024)
A new historical re-construction about the plot occupation in Santiago between 1980 to 1984 and the participation of the Communist Party are proposed in this article. Going to the publications of that period, both from the opposition and in favor to the regime opinion, plus the documents of the Party, expose the facts and the consequences there were inside the political organization, regarding to the failures and successes that these invasions had into the private property. From these actions, it is tried to explain that the plot occupations and slum settlement building, together to protests, the violence executed by the masses in the neighborhoods and the FrentePatriotico Manuel Rodriguez armed actions were an important issue in the analysis of the Party to determine in the plenary session in 1984 that there were enough conditions to establish the dictatorship fall.